Developmental Timing of the Male-Female Health-Survival Paradox. Issue 2 (October 2014) - Draper, Thomas W.; Abrahamson, Hayley
A sample of 200, 000 men and women was used to examine the paradoxical observation that in old age there are more women than men but the men are in better health. Insofar as subsequent one-year survivability can be used as an index of health, the paradox was partially supported. After 99 years of age, there was a period of time when men's health compared to women's was improving relative to what it was previously. But there was never a time when it was actually better. The possibilities remain that earlier reports of the paradox might be the result of (a) sample limitations, (b) a focus on types of health that are unrelated to subsequent survival, or (c) local behaviors or conditions, such as smoking or air pollution, that can influence the health of men and women differently.